Synthesis Bioactivities and Non-linear Optical Behavior of Angularly and Linearly Fused Pyridazino Quinoline Derivatives - Radhakrishnan, Namitha; Gopal, Selvi (Asian Journal of Biological and Life Sciences)
Angularly and linearly fused pyridazino quinolines has been reported via the cyclisation of hydrazino quinoline with chloroacetyl chloride. The structure was characterized by IR and NMR studies. The synthesized chemical compounds were applied against 2 gram-positive bacteria and 2 gramnegative bacteria by the well diffusion method. The entire synthesized compounds exhibited different degrees of antimicrobial activity at concentrations between 20–100 μg/disc against the test organisms. Antioxidant studies were also performed against DPPH radical and the results were attractive. In vivo anti-inflammatory and analgesic screening was also done for selected drug and the results were desirable. Quantum chemical calculations were performed using the DFT B3LYP method in the 6-31G (d, p) basis. Non-linear optical behavior of the compounds was analyzed by with first hyperpolarisability. The non-linear optical properties of solution of compound in DMSO solvent has been investigated using Z-scan technique with femto second. The calculated value of non-linear absorption coefficient displayed the non-linearity of the molecule. The in silico ad instrumental results showed that the compounds are attractive molecules for future application in non-linear optics.
Keywords: Analgesic; Antiinflammatory; Carrageenan; Chloroacetyl chloride; Pyridazine; S. aureus